1993
DOI: 10.1111/j.1476-5381.1993.tb13770.x
|View full text |Cite
|
Sign up to set email alerts
|

Glycine stimulates striatal dopamine release in conscious rats

Abstract: 1 Glycine is an inhibitory neurotransmitter in the spinal cord and brainstem. The mechanism of this inhibition is via binding of glycine to specific receptors, increasing transmembrane Cl-conductance and hyperpolarizing neurones. Strychnine selectively antagonizes these effects. The role of glycinergic neurones in supraspinal regions is poorly understood. 2 Effects of glycine on release of catecholamines in the striatum were examined by microdialysis in freely-moving rats. Transcription of the genes encoding s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
76
0

Year Published

1996
1996
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(83 citation statements)
references
References 22 publications
7
76
0
Order By: Relevance
“…In the central nervous system, glycine and these receptors mediate inhibitory neurotransmission in the same manner as GABA and work simultaneous with GABA (Legendre 2001;Lopez et al 2001). Moreover, it was revealed that glycine injection increases dopamine concentration in the rat striatum interstitium (Yadid et al 1993). Thus, we examined whether theanine increased interstitial glycine concentration and whether glycine neurotransmission contributed to the increase in interstitial dopamine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the central nervous system, glycine and these receptors mediate inhibitory neurotransmission in the same manner as GABA and work simultaneous with GABA (Legendre 2001;Lopez et al 2001). Moreover, it was revealed that glycine injection increases dopamine concentration in the rat striatum interstitium (Yadid et al 1993). Thus, we examined whether theanine increased interstitial glycine concentration and whether glycine neurotransmission contributed to the increase in interstitial dopamine.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, some studies suggested that dopamine could modify glutamate neurotransmission. (Moghaddam et al 1990;Yadid et al 1993;Koga and Momiyama 2000). Because the chemical structure of theanine is similar to glutamic acid, some studies of theanine examined its relationship to glutamic acid function and metabolism (Sugiyama et al 2003;Kakuda et al 2002a;Tsuge et al 2003;Oda et al 1980); however, the glutamate receptor antagonist MK-801 did not affect the increase of dopamine concentration by theanine injection in the rat striatum (Yokogoshi et al 1998a).…”
Section: Discussionmentioning
confidence: 99%
“…This serotoninergic hyperinnervation, often observed in animal models of PD (Zhou et al, 1991;Gaspar et al, 1993;Yamazoe et al, 2001), may be compensatory. Indeed, 5-HT may promote DA release from the remaining dopaminergic fibers (Benloucif and Galloway, 1991;Yadid et al, 1994). Finally, the correlation between 5-HT concentration in the associative-limbic territory and recovery time strongly suggests a role for 5-HT in recovery.…”
Section: Relevance Of Repeated Microdialysis For Investigating Neurocmentioning
confidence: 99%
“…Many neurochemical studies demonstrate this relationship (Nurse et al 1988;Blandina et al 1988;Yi et al 1991;Jacocks and Cox 1992;Hallbus et al 1997;Benloucif and Galloway 1991;Parsons and Justice 1993;Yadid et al 1994;Yoshimoto et al 1996). The 5-HT-DA interaction question has been approached in an elegant and novel way by Broderick and Phelix (1997).…”
Section: -Ht-da Interactions In Reward and Motor Behavior 449mentioning
confidence: 99%